Pengaruh Perubahan Nilai Tukar dan Suku Bunga SBI pada Perubahan Harga Saham Bank Pemerintah di Bursa Efek Indonesia - Rahmiati, Tetty Sari (Business and Management Review, 2010)
The banking sector is a sector that plays an important role in supporting the economy of the entire program in Indonesia. Is Bank Mandiri Tbk, PT Bank Negara Indonesia Tbk and Bank Rakyat Indonesia that state banks that play a role in supporting government policy. Although banks are government-owned, but not out of the participation of the investors who invest in shares. Has the price or value of shares to be bought and sold. Theoretically, the increase or decrease in the stock price is influenced by several factors, including the value of the rupiah against the dollar and interest rates SBI. This study aims to analyze the effect of changes in the exchange rate against the dollar and the SBI interest rate on stock prices of banks by the government. The research method used is the correlation and regression analysis with SPSS. From the analysis using SPSS, we got the result that; together changes the value of the rupiah against the dollar and the SBI interest rate changes affect the stock price of Bank Mandiri Tbk. While SBI individually had no effect on stock price changes of Bank Mandiri Tbk.. Conclusions generated in this study for the three state-owned banks is variable changes in the exchange rate against the dollar and interest rates affect tehadap SBI Bank share price Mandri Tbk Keywords: exchange rate, interest rates, stock prices